The interesting case: orphan diseases : double trouble - Reuner, Ulrike; Stremmel, Wolfgang; Weiskirchen, Ralf (Annals of translational medicine, 2019)
With an incidence of 1:20,000-1:30,000, Wilson’s disease is regarded as a rare disease. Yet rarer, however, is the co-occurrence of two unrelated orphan diseases in the same patient. By means of two case reports, we would like to illustrate the necessity of an appropriate differential diagnostic evaluation and treatment of these disorders.
Gesehen am 21.10.2019